2020
DOI: 10.1002/msc.1474
|View full text |Cite
|
Sign up to set email alerts
|

Educational needs of patients with rheumatic and musculoskeletal diseases attending a large health facility in Austria

Abstract: Introduction Patient education is an important part of the management of rheumatic and musculoskeletal diseases. Given that patients with diverse diseases do not have the same needs, it is crucial to assess the educational requirements of targeted groups to provide tailored educational interventions. The aim of our study was to assess educational needs of a large cohort of patients with different rheumatic and musculoskeletal diseases attending a health facility in Austria. Methods We assessed educational need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, no other studies on patient education in the field of rheumatology have investigated whether patients' educational needs change over time. Other studies have mainly focused on whether patients have different needs depended on diagnosis (Hirsch et al, 2020), disease activity or demographic characteristics (Bremander et al, 2018;Haglund et al, 2017). This study did not detect any associations between patients' total educational needs and diagnosis, but other studies have shown that patients with Spondyloarthritis report higher needs for education on pain and movement (Bremander et al, 2018), patients with Rheumatoid Arthritis want more education on treatments, and patients with fibromyalgia have higher needs for education about feelings (Hirsch et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…To the best of our knowledge, no other studies on patient education in the field of rheumatology have investigated whether patients' educational needs change over time. Other studies have mainly focused on whether patients have different needs depended on diagnosis (Hirsch et al, 2020), disease activity or demographic characteristics (Bremander et al, 2018;Haglund et al, 2017). This study did not detect any associations between patients' total educational needs and diagnosis, but other studies have shown that patients with Spondyloarthritis report higher needs for education on pain and movement (Bremander et al, 2018), patients with Rheumatoid Arthritis want more education on treatments, and patients with fibromyalgia have higher needs for education about feelings (Hirsch et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…Other studies have mainly focused on whether patients have different needs depended on diagnosis (Hirsch et al, 2020), disease activity or demographic characteristics (Bremander et al, 2018;Haglund et al, 2017). This study did not detect any associations between patients' total educational needs and diagnosis, but other studies have shown that patients with Spondyloarthritis report higher needs for education on pain and movement (Bremander et al, 2018), patients with Rheumatoid Arthritis want more education on treatments, and patients with fibromyalgia have higher needs for education about feelings (Hirsch et al, 2020). We did not investigate associations between diagnoses and different educational domains, but we found that females have larger total educational needs than men, which was supported by the systemic review by Connelly and co-workers (Connelly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some systematic reviews have examined the effect of educational interventions on patients’ pain experience in various acute and chronic pain conditions (eg, post-surgery, musculoskeletal pain, whiplash injuries, cancer) 7–10 . These reviews have either shown no benefit or a modest effect on pain and associated disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The ENAT is a self-administered questionnaire that can also be used by researchers to determine the educational needs of the patient at the time of administration. In an online survey of educational needs of patients with various rheumatic and musculoskeletal diseases (RMDs), Hirsch et al identified that the educational needs of patients vary by disease groups and that healthcare professionals need to assess disease-specific needs for education in order to achieve high quality of care [13].…”
Section: Introductionmentioning
confidence: 99%